Vaccination coverage of women in the postpartum pregnancy cycle at an outpatient clinic of a School Hospital (Research, Society and Development, 2020)
The present study aimed to analyze the vaccination coverage of pregnant women and postpartum women attended at the Integrated Medicine Obstetrics outpatient clinic of the School Hospital in a city in the interior of the State of Rio de Janeiro. This was a descriptive exploratory study with a quantitative approach, collected at the Integrated Medicine Clinic (AMI) of School Hospital. Data were collected and analyzed using a minimum sample of 100 women attended at the AMI, with the eligibility criteria being pregnant or postpartum women. Still in the data analysis, the characterization of the clientele and the calculation of the vaccine coverage specifically for this sample were carried out. 100 women participated in the research, 83% of whom were pregnant and 17% who had recently given birth, 44% of those interviewed aged 25 to 30 years old and 41% with completed high school. Among pregnant women 47% had 07 or more prenatal consultations, 35% were in the first pregnancy and 28% were 28 or more weeks pregnant. Among the puerperal women 82% had 07 or more prenatal consultations, 76% had 01 postpartum consultation and 47% were in the second pregnancy. Regarding vaccination coverage, 62% were vaccinated with tetanus, 54% with DTpa, 60% vaccinated against Hepatitis B, 70% against H1N1 and 61% were vaccinated against Yellow Fever. It is concluded that there is a need for attention to the vaccination situation of pregnant women, and the immunobiologicals necessary to prevent diseases during pregnancy and the puerperium are below 80%, when the minimum recommended by the Ministry of Health is 95%.